1954
DOI: 10.1107/s0365110x54000989
|View full text |Cite
|
Sign up to set email alerts
|

`β-Tungsten' as a tungsten oxide

Abstract: The existence of 'fl-W' as a modification of tungsten is contradicted by the low density of the phase and by its decomposition into W and WO,. at about 700°C. It is assumed that 'fl-W' is a metallic tungsten oxide with the probable ideal formula W30. The unit cell would then contain 6 W+20 atoms distributed at random over the eight positions of the A15 structure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
48
0
1

Year Published

1992
1992
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(50 citation statements)
references
References 2 publications
0
48
0
1
Order By: Relevance
“…However, careful analysis of this and further SAED patterns, such as that shown in the inset to Figure 3 d, which approaches a [21 1 0] projection, yields a more precise match to 2H-TaS 2 than to 1T-TaS 2 . The 3R and less-common 6R polytypes [9,17] were also considered, but neither provided an acceptable match to the SAED data. Therefore, the SAED data are consistent with the predominant phase of the nanowires being 2H-TaS 2 .…”
mentioning
confidence: 99%
“…However, careful analysis of this and further SAED patterns, such as that shown in the inset to Figure 3 d, which approaches a [21 1 0] projection, yields a more precise match to 2H-TaS 2 than to 1T-TaS 2 . The 3R and less-common 6R polytypes [9,17] were also considered, but neither provided an acceptable match to the SAED data. Therefore, the SAED data are consistent with the predominant phase of the nanowires being 2H-TaS 2 .…”
mentioning
confidence: 99%
“…Refs. [31,39,40,45] The solid solubility of Sb in α(A2) is 3 at% Sb at low temperature reported by Hägg [39,40] and 3.8 at% Sb at 1261 K by Geller [33].…”
Section: Phase Equilibrium Informationmentioning
confidence: 94%
“…[31,32,[37][38][39][40][41][42][43][44] showed that the homogeneity range of β (FeSb) is shifted to higher Sb contents with decreasing temperature. Refs.…”
Section: Phase Equilibrium Informationmentioning
confidence: 99%
“…Still under debate, [45] the structure of the Pm3 n micellar cubic phase is thought to be made of two types of micelles: two quasispherical ones are located at the corners and center of the cubic lattice, and six with a more flattened shape are positioned in the middle of the faces. [46] This latter structure was proposed after the so-called A15 [47] structure known in metal alloys (MM' 3 ) and metal oxides (MO 3 ). In this case, the atoms M generate a cubic body-centered substructure (i.e., Im3 m symmetry), and each of the cubic faces contains a pair of the M' or O atoms located on two of the four tetrahedral sites, leading to breaking up of the symmetry.…”
Section: Supramolecular Organization and Modelingmentioning
confidence: 99%